واقع النقل السياحي الأخضر بإمارة دبي: The reality of green tourism transport in the Emirate of Dubai - قعيد لطيفة (Journal of North African Economies, 2025)
Transport activity is increasing all over the world with the growth of economies, which means that the emissions of gases from the sector are increasing as well, due to the fact that 95% of the transport capacity in the world still comes from fossil fuels. Dubai is considered one of the countries with a great tourist position in the Gulf region, and many factors contributed to its reaching that status. This study aims to focus on one of these factors, which is transport, which helped increase the number of tourists coming to the emirate year after year, and the study concluded that The Emirate of Dubai has made intensive and coordinated efforts to provide green transportation means to reduce the negative environmental impacts resulting from transportation activities, with the help of effective environmental management systems, energy, and the latest technology.